2013
DOI: 10.1007/s00436-013-3707-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and diversity of Encephalitozoon spp. and Enterocytozoon bieneusi in wild boars (Sus scrofa) in Central Europe

Abstract: From 2011 to 2012, the occurrence of Enterocytozoon bieneusi and Encephalitozoon spp. was surveyed at 29 randomly selected localities (both forest areas and enclosures) across four Central European countries: Austria, the Czech Republic, Poland, and the Slovak Republic. Isolates were genotyped by PCR amplification and characterization of the internal transcribed spacer (ITS) region using Enterocytozoon and Encephalitozoon-specific protocols. PCR revealed 16 mono-infections of Encephalitozoon cuniculi, 33 mono-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 39 publications
5
41
2
Order By: Relevance
“…The close genetic relationship of genotypes G and NECA1 to NECA5 with many human-pathogenic genotypes in group 1 is also of potential zoonotic concern. In addition to cattle, genotype G also existed in pigs from China and Germany, horses and wild boar from the Czech Republic, and a drinking water source in China, and genotype CS-4 was found in pigs from China (4,14,38,49,50). We concluded that cattleharbored E. bieneusi genotypes have zoonotic potential and are implicated in public health.…”
Section: 36mentioning
confidence: 85%
“…The close genetic relationship of genotypes G and NECA1 to NECA5 with many human-pathogenic genotypes in group 1 is also of potential zoonotic concern. In addition to cattle, genotype G also existed in pigs from China and Germany, horses and wild boar from the Czech Republic, and a drinking water source in China, and genotype CS-4 was found in pigs from China (4,14,38,49,50). We concluded that cattleharbored E. bieneusi genotypes have zoonotic potential and are implicated in public health.…”
Section: 36mentioning
confidence: 85%
“…The percentages of zoonotic genotypes were observed to vary in different countries or different areas within a country, ranging from 33.3% to 100% (Table 1). We also noticed that all the E. bieneusi isolates were identified as zoonotic in two studies conducted in Austria and the Czech Republic (17,30). However, the risk that pigs pose to humans might be greater in the Czech Republic than in Austria, as a higher occurrence of E. …”
Section: Discussionmentioning
confidence: 69%
“…The internal transcribed spacer (ITS) region of the rRNA gene is most commonly used in genotyping E. bieneusi isolates. To date, besides humans, it has been isolated from pigs, wild boars, macaques, dogs, cats, cattle, llamas, horses, gorillas, baboons, raccoons, muskrats, beavers, foxes, otters, chickens, pigeons, parrots, sparrows, aquatic birds, and falcons (15)(16)(17)(18)(19). The finding of the same ITS genotypes of E. bieneusi in humans and animals supported the possibility of zoonotic transmission.…”
mentioning
confidence: 75%
See 2 more Smart Citations